Double vascularized omentum lymphatic transplant (VOLT) for the treatment of lymphedema. Issue 7 (8th March 2018) - Kenworthy, Elizabeth O.; Nelson, Jonas A.; Verma, Richa; Mbabuike, JeanJacques; Mehrara, Babak J.; Dayan, Joseph H.
Abstract : Background and Objectives: Orthotopic vascularized lymph node transplant has been successfully used to treat lymphedema. A second, heterotopic lymph node transplant in the distal extremity may provide further improvement. The vascularized omentum lymphatic transplant (VOLT) provides adequate tissue for two simultaneous flap transfers to one limb. The purpose of this study was to review our experience with this technique. Methods: We conducted a retrospective study of patients who underwent VOLT, with a subgroup analysis of patients who underwent double VOLT. Technical aspects of the procedure, complications, and early outcomes were reviewed. Results: From May 2015 to August 2017, 54 VOLTs were performed in 38 patients, of whom 16 received double VOLT. Among patients in the double VOLT group with postoperative imaging at 1 year, uptake into the transplanted omentum was seen in three of six (50%) patients on lymphoscintigraphy and in one of five (20%) patients on indocyanine green lymphangiography. One patient (3.1%) in the double VOLT group required a return to the operating room. There were no donor site complications in the double VOLT group. The overall complication rate was 15.8%. Conclusions: Double VOLT to the mid‐level and proximal extremity is a safe and viable option.